El precio de la libertad de los remensas (Gerona, siglos xiv-xv) - Rosa Lluch Bramon (Les Cahiers de Framespa)
Catalan serfs, that is to say, the remences, could have a price: the price of their own freedom. In fact, since they had to pay the so called remença (redemption) in order to purchase their own freedom, they received that name. The aim of this work is to study the price of remences’ freedom during the fourteenth and fifteenth centuries. First of all, we analyse the theory explained by the Customs of Gerona and, secondly, we study all the redemptions granted by a feudal lordship of Gerona.